Mothering a neonate/young infant with feeding and swallowing difficulties: barriers, facilitators, and support - Meyer, Cecilia (Department of Health and Rehabilitation Sciences, 2026)
Background: The anticipation of a new infant is typically characterised by feelings of joy, excitement, and hopeful expectations for the future. However, these positive emotions can be altered when mothers are faced with the reality of caring for an ill, hospitalised infant, particularly one with feeding and swallowing difficulties (FSD). FSD in infants significantly impacts not only the infant's health and development but also the mother's emotional and psychological wellbeing. Caring for neonates and young infants with FSD in hospital settings presents unique challenges, especially in resource-constrained environments like South Africa. Limited research exists exploring mothering an infant with FSD, highlighting a gap in understanding the maternal experience. Research aim and objective: This research aimed to explore ‘mothering' a neonate/young infant with FSD in a South African healthcare context. To achieve the aim, mothers' experiences of barriers, facilitators and support needs within a neonatal healthcare context are described. Methods: A qualitative, exploratory case study design was used. Semi-structured interviews were conducted with mothers whose infants presented with FSD in neonatal/infant units. A total of seven mothers were interviewed (n=7) whose infants (aged from birth to three months) were admitted at either Mowbray Maternity Hospital or Red Cross War Memorial Children's Hospital, for a minimum of seven days. The data were thematically analysed, allowing the emergence of key themes that represent maternal experiences. Results: The overarching theme of ‘mothering' emerged, encapsulated by the quote: “Baby comes first in everything.” Six distinct themes then emerged from the overarching theme, represented by relevant quotes from the participants: “Information helps”; “They help a lot”, “It's not home”, “Everything on you”, “It affects me emotionally”, “Not on your own” and lastly, “It's my baby”. These themes emerged from the accounts of the mothers, which were then described in terms of barriers such as separation and burden of care, facilitators such as information and maternal strength, and support structures. The findings outline the dedication and resilience of mothers when navigating the challenges of caring for infants with FSD, while also highlighting the intricate and often dichotomous realities they face in the hospital setting. Conclusion: This study highlights the complex experiences of mothers caring for infants with FSD in South African healthcare settings. While deeply committed to their infants' wellbeing and feeding, mothers face barriers such as inadequate communication, separation, and limited support, which heighten stress and guilt. Facilitators, including clear communication, practical support from healthcare professionals, and peer and family networks empower mothers and alleviate their emotional burden. A collective effort by healthcare professionals, families, and hospital systems is essential to ensure care that supports both the recovery of infants and the wellbeing of their mothers. These insights can inform healthcare practices and future research in similar resource-limited settings.